Bukhta Morzhovai︠a︡ po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1919 g. / Sʺemka i cherchenīe Shturmana dal. pl. Ivanovskago - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1919)
Relief shown by form lines, hachures and spot heights. Depth shown by soundings and isolines.; Coordinates for Morzhovaya Bay given on map: 53°14'05.6"N 159°57'24.0"E.; Greenwich meridian.; "No. 405" -- top right margin Grayscale; 1:21,000